Perceptions of research participation among underrepresented groups: Insights using freelisting methodology - Tamar Klaiman; Jasmine A. Silvestri; Emma Britez Ferrante; Dorothy Sheu; Adina Lieberman; Erich Dress; Modele O. Ogunniyi; Neal W. Dickert; Meghan B. Lane-Fall; Rosemary Frasso; Rachel Kohn (PLoS ONE, 2026)
Background Low enrollment and retention in clinical research disproportionately impact Black, Hispanic or Latinx, women, and rural populations, undermining generalizability and perpetuating health disparities. However, few studies have compared mechanisms driving underrepresentation across populations. Freelisting is a qualitative methodology that elicits lists of terms, explores perspectives about domains, and identifies common themes within groups with shared characteristics; however, it has not been systematically applied to understand research participation across underrepresented populations. Objective To explore perspectives on clinical research participation across underrepresented populations using freelisting methodology to ultimately inform culturally-responsive recruitment strategies. Methods We conducted a web-based freelisting survey among adults who identified as Black, Hispanic or Latinx, women, and/or resided in rural communities between May and September 2023 across the Philadelphia, Atlanta, and Washington, DC metro areas. Participants listed words or phrases that came to mind in response to three prompts about research and participation. Using Anthropac software, we calculated salience indices to assess the relative importance of terms within and across the underrepresented groups. Terms were categorized by sentiment (positive, neutral, negative) and examined by demographic group and prior research experience. Results Of 101 participants (56% Black, 23% Hispanic or Latinx, 80% women, 46% rural), several salient terms were shared, including ‘study,’ ‘knowledge,’ ‘search,’ and ‘scary.’ Sentiment regarding being approached for research was generally positive. In contrast, sentiment about becoming a participant varied, with more negative terms among those never previously invited to join research. ‘Research misconduct’ emerged as uniquely salient among Black participants. Individuals with prior research experience conveyed more positive sentiments overall. Conclusions Underrepresented populations hold positive and negative views about clinical research, with more negative perceptions among those never previously approached. These findings suggest that proactive outreach to individuals who have never previously been approached, combined with efforts to address persistent negative perceptions such as fear, may be among the most impactful strategies for improving research representativeness. Future work is needed to understand the contextual information surrounding the sentiments we found, and to elucidate the mechanisms underlying these sentiments, ultimately enabling the development of more effective, culturally-responsive recruitment and retention strategies across diverse groups.